Operational amplifiers - Clayton, George
George Clayton's Operational Amplifiers is a well established undergraduate text - offering full coverage of the subject for HNC/HND electronic engineering as well as first and second year degree modules. It has also proved popular in industry as a reference text. Having previously been fully revised by Steve Winder, this classic textbook covers all the latest developments in the field, matched to current degree module syllabuses in both the UK and USA. The introductory sections assume only a basic grounding in electronics, followed by more in-depth material to further the reader's understanding.